A cross sectional analysis on the clinical presentation and outcome of H1N1 influenza patients in a tertiary care hospital in Central Kerala - George, Alvin Treasa; George, Grace; Simson, David K.; Antony, T. P. (International Journal of Advances in Medicine, 2019)
Background: The World Health Organization raised pandemic H1N1 influenza alert level to phase 6 in June 2009 due to a widespread community transmission on two continents. The recent surge in positive H1N1 cases necessitates a revisit to the clinical profile of the 2009 pandemic. This study was aimed to analyse the clinical profile and outcome of swab positive H1N1 patients. Methods: A cross sectional analysis on the clinical presentation and primary out come in the confirmed H1N1 influenza cases was done. H1N1 confirmation was done using real time reverse transcriptase-Polymerase Chain Reaction in throat swab samples. The data were analysed statistically and presented in percentage. Results: Total 31 cases of severe H1N1 were included in the study. Majority of the cases (16/31) were between15 to 30 yrs of age. Among the total cases, 27 cases were females (87.1%) of which 11 cases were pregnant (35.5%). The predominant presenting symptoms were fever (100%), breathlessness (80.6%), body ache (45.2%), headache (29%) and sore throat (29%). Twenty three of the 31 patients (74.2%) survived while 8 succumbed to the illness (25.8%). All the patients required ICU admission and 8 underwent invasive ventilation. The mortality was high among the ventilated patients (p=0.0064). Conclusions: Pregnancy was associated with higher rate of complications. Early respiratory support did not help in preventing progression to respiratory failure in most of the patients. Vaccination, early recognition of the disease and prompt initiation of treatment appear to be the only way to reduce H1N1 disease progression and mortality.